PEMBERDAYAAN MASYARAKAT MELALUI PEMANFAATAN LIMBAH MINYAK JELANTAH MENJADI SABUN PEMBERSIH LANTAI DI DESA KARYA INDAH KECAMATAN TAPUNG KAMPAR - Imelda Yunita; Erpiani Siregar; Resdati -; Mun Holidah; Gabriel Jose Gilbert Simanjuntak (Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
One household waste that has an impact on the environment is used cooking oil (used cooking oil). Used cooking oil can pollute the environment if it is simply dumped into the environment. The impact is like the potential for soil and water damage. One way that can be done to overcome the problem of environmental pollution is to diversify used cooking oil by processing it into valuable products such as making floor cleaning soap. Used cooking oil has economic potential if it can be managed properly. The purpose of this community service is to increase the knowledge and skills of housewives in processing used cooking oil waste into floor cleaning soap. The method of community service activities is counseling and training in making floor cleaning soap. The community service activities were carried out at Gravindo 1 Housing which was attended by housewives in Tapung District, Kampar Regency, Riau. The results of the community service activities that have been carried out based on the results of the Pre Test and Post Tets, namely before the training activities are carried out, it is known that housewives do not know that used cooking oil can be used as an ingredient in making floor cleaning soap and the procedure for making floor cleaning soap. After the counseling and training activities were given according to the results of the Pre Test, there was an increase in housewives' knowledge about the utilization of used cooking oil into floor cleaning soap and procedures for making floor cleaning soap. Conclusions and recommendations from this service activity are that it can increase the knowledge and skills of housewives in making floor cleaning soap. It is hoped that similar activities will also be implemented in various places to be able to overcome the problem of used cooking oil waste and increase knowledge and skills for the community in utilizing waste into useful and economically valuable products.